INCREASING THE PRODUCTIVITY OF THE FURNITURE INDUSTRY WITH KAIZEN CASE STUDY IN SBRC FURNITURE JEPARA - Antonius Cahyono; Muhamad Abdul Jumali; Rusdiyantoro Rusdiyantoro (Journal of Industrial Engineering Management, 2023)
In the era of economic digitalization, global business and industry competition is very tight and moves fast. Fashion, trends, and innovations are growing vigorously so that all business and industry players continue to increase their productivity in all fields. The increase in productivity is in line with the company's efforts to increase profits along with optimal product and service quality to consumers. However, efforts to increase it will be hampered by several aspects of waste, this is what is felt by small and medium business actors such as SBRC Furniture which is engaged in the production of carving frames. This research aims to identify various wastes that occur by changing them through the Kaizen method to provide constructive notes to increase business productivity.